ON THE OCCURRENCE OF MACROBRACHIUM LAMARREI (H. MILNE EDWARDS) IN THE RAMGARH LAKE, GORAKHPUR, WITH A NOTE ON THE VARIATIONS OF ITS ROSTRAL CHARACTERS - Omkar, Ram Murty; Shukla, G S (Indian Journal of Fisheries, 2011)
The occurrence of Macrobrachiitm lamarrei (H. Milne Edwards) in theRamgarh lake, Gorakhpur, is reported. A detailed study of this M. lamarreishowed some differences in the rostral characters when compared to the previouslyknown subspecies M. lamarrei lamarrei and M. lamarrei lamarroides(Tiwari 1952). These difference are discussed